1999
DOI: 10.1097/00004647-199910000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Survival- and Death-Promoting Events after Transient Cerebral Ischemia: Phosphorylation of Akt, Release of Cytochrome C, and Activation of Caspase-Like Proteases

Abstract: Release of cytochrome c (cyt c) into cytoplasm initiates caspase-mediated apoptosis, whereas activation of Akt kinase by phosphorylation at serine-473 prevents apoptosis in several cell systems. To investigate cell death and cell survival pathways, the authors studied release of cyt c, activation of caspase, and changes in Akt phosphorylation in rat brains subjected to 15 minutes of ischemia followed by varying periods of reperfusion. The authors found by electron microscopic study that a portion of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(150 citation statements)
references
References 39 publications
12
134
3
1
Order By: Relevance
“…Because all mitochondrial toxins used in this study cause energy failure, which in turn induces calcium influx into mitochondria, this is one possible mechanism of mitochondrial dysfunction, which would explain why activation of DNA repair enzymes can paradoxically enhance cell death (31), presumably through energy depletion, and would imply that other types of mitochondrial malfunction may well trigger similar cascades. This hypothetical mechanism would also explain the relationship between energy failure and excitotoxicity, both of which might trigger calcium accumulation and cytochrome c release, and the reports of a necrotic morphology (7,8) and an apoptotic-like biochemistry (32)(33)(34)(35) in pathological situations characterized by depletion of energy reserves, such as cerebral ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…Because all mitochondrial toxins used in this study cause energy failure, which in turn induces calcium influx into mitochondria, this is one possible mechanism of mitochondrial dysfunction, which would explain why activation of DNA repair enzymes can paradoxically enhance cell death (31), presumably through energy depletion, and would imply that other types of mitochondrial malfunction may well trigger similar cascades. This hypothetical mechanism would also explain the relationship between energy failure and excitotoxicity, both of which might trigger calcium accumulation and cytochrome c release, and the reports of a necrotic morphology (7,8) and an apoptotic-like biochemistry (32)(33)(34)(35) in pathological situations characterized by depletion of energy reserves, such as cerebral ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have also provided additional evidence of caspase-3 activation in other models of cerebral ischemia following strokes in adults and neonates. This includes the mitochondrial release of cytochrome c and activation of caspase-9, a proximal caspase in the caspase-3 apoptotic cascade (Gillardon et al, 1997;Cheng et al, 1998;Namura et al, 1998;Pulera et al, 1998;Kiprianova et al, 1999;Krajewski et al, 1999;Ouyang et al, 1999;Velier et al, 1999;. Several recent studies using caspase inhibitors provide support of these original observations, and demonstrate that injury severity can affect the efficacy of caspase inhibitors in reducing cell death.…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 88%
“…29 The PI3K-AKT pathway has been attributed a major role in the protection of neurons from caspase-mediated cell death after brain ischemia. 30 Phosphorylation of AKT at serine 473 was increased after several minutes of reperfusion and was sustained for days following ischemia. 8 In turn, it was shown that CHIP promotes downregulation and degradation of phosphatase and tensin homolog (PTEN), a negative modulator of AKT phosphorylation, which increases the levels of p-AKT.…”
Section: Discussionmentioning
confidence: 99%